'A collection of mere travesties of time-honoured originals': The rejection of the Shipley bequest. (7th April 2020) - Anguix, Laia
Abstract: In 1909 the city of Newcastle was offered the bequest of J.A.D. Shipley. Containing 2, 500 paintings attributed to masters such as Rembrandt and Raphael, and linked to a sum of £30, 000 for museum accommodation, it caused a media stir. C. B. Stevenson, curator of the Laing Art Gallery in Newcastle upon Tyne, reported that the collection contained many 'feeble imitations . . . unworthy of the names attached to them.' 1 Nevertheless, he recommended its acceptance, because of the benefit it would confer on the Laing. But Newcastle council rejected Stevenson's advice, favouring external reports to support its verdict, which was based on financial concerns and on the negative responses of prominent citizens. The Laing's appeals were disregarded and Gateshead obtained the bequest, leading to the creation of the town's first public art gallery, the Shipley Art Gallery, in 1917. The Shipley case is here discussed as an example of misunderstanding between cultural institutions and political structures, and of the power of local elites to raise questions regarding authorship and authenticity.